Regulation of the Thrombotic Potential of Atheroma - Libby, Peter; Mach, François; Schönbeck, Uwe; Bourcier, Todd; Aikawa, Masanori (Thrombosis and Haemostasis, 1999)
Thrombosis underlies most acute manifestations of atherosclerosis and likely is an important contributor to the evolution of atherosclerotic lesions. In the coronary arteries, thrombosis precipitates most episodes of unstable angina and acute myocardial infarction (both Q-wave and non Q- wave). But, of course, atherosclerosis is a systemic disease that affects many arterial beds. Thus, the thrombotic complications of atherosclerosis also cause many strokes and acute exacerbations of peripheral vascular disease that place limbs in jeopardy.Many studies have clarified the microanatomy of fatal coronary thrombosis. Flow limiting stenoses were formerly considered the cause of the acute coronary syndromes. Recent clinical observations, however, have taught us that most myocardial infarctions result from thrombi that occur on the substrate of a lesion that does not cause a critical narrowing of a coronary artery. We now appreciate that a physical disruption of the atheromatous plaque most often provokes thrombus formation. Plaque disruption takes two major forms: a frank fissuring of the plaque’s fibrous cap and a superficial erosion of the intimal surface (Table 1). In the case of a ruptured cap, blood coagulation factors come into contact with the plaque’s lipid core, which is rich in tissue factor and considered the major procoagulant in this situation. In the case of superficial erosion, platelets can contact subendothelial basement membrane and collagen within the plaque, which may trigger platelet aggregation. Additionally, smooth muscle cells underlying the endothelium can also express tissue factor, further contributing to thrombus formation.Excellent evidence suggests that plaque rupture occurs frequently, even in asymptomatic individuals. Consequently, most arterial thrombi do not produce clinical manifestations. Presumably, most mural thrombi either fail to occlude the vessel, as they do not propagate, or are evanescent. A healing mural thrombus, although clinically silent, may still contribute to plaque growth. Platelets contain potent fibrogenic mediators, such as platelet-derived growth factor (a smooth muscle cell chemoattractant) and transforming growth factor (TGF)-β (a strong stimulus to smooth muscle collagen gene expression). Thrombin and activated factor X can stimulate smooth muscle cell proliferation by direct and/or indirect routes. These mediators may link healing mural thrombi in arteries to intimal growth and the formation of stenotic lesions.Why do some plaque disruptions lead to an occlusive thrombus that may cause sudden death, while other disruptions pass unnoticed? The locally prevailing hemostatic and fibrinolytic balance likely proves decisive in determining the fate of a given disruption of an atheroma. Much evidence has recently accumulated regarding the factors that regulate these regional balances. This chapter will selectively summarize certain of those recent findings. It will also provide some mechanistic insight into how contemporary therapies may act to reduce the thrombotic complications that cause the most dreaded and dramatic complications of atherosclerosis.